Investigation on indoor visible light positioning systems - Lei, Lei (Nanyang Technological University, 2020)
With the development of communication technology, there are some shortcomings been found in wireless communication in terms of radio waves. For example, the limitation of the available spectrums. In order to tackle the bandwidth problem, the Light Fidelity (LiFi) technology is hence produced which is a new kind of communication method to transmit data using visible light proposed by a team from the University of Edinburgh [1].